Preparation of high performance nanofiltration (NF) membranes incorporated with aquaporin Z - Wicaksana, Filicia (2013)
Aquaporin (AQP) based biomimetic membrane has attracted increasing attention in recent years because of its potential application for water purification and seawater desalination, attributed to the exceptionally high permeability and selectivity of AQPs. Despite its superior performance, AQP based membrane faces several challenges associated with the design and preparation of such membranes for practical application. In this current study, a novel and simple method was introduced to prepare an aquaporin Z (AqpZ) based biomimetic nanofiltration (NF) membrane with a relatively large membrane area of 28.26 cm2. The proteoliposome, incorporated with AqpZ, was fully encapsulated into the selective layer through crosslinking of a polyelectrolyte with the membrane substrate made by poly(amide–imde) (PAI). The water flux of the AqpZ based membrane was around 50% higher than the mutant one. At optimal preparation conditions, the AqpZ based membrane could offer a water flux of 36.6 L m−2 h−1 with a MgCl2 rejection of 95% at 0.1 MPa. Results from this study showed that AqpZ could maintain its activity even under harsh environmental conditions of thermal treatment at 343 K for 2 h. These results and findings may provide useful insights on developing next generation of biomimetic membranes.